Comparison of Anti-Microbial Effects of Low-Level Laser Irradiation and Microwave Diathermy on Gram-Positive and Gram-Negative Bacteria in an In Vitro Model - Snehil Dixit; Irfan Ahmad; Abdulrahim Hakami; Kumar Gular; Jaya Shanker Tedla; Mohammed Abohashrh (Medicina, 2019)
Background and Objectives: The aim of this study was to compare the effects of low-level laser therapy and continuous microwave diathermy on the growth of Gram-negative and Gram-positive bacteria and to establish their efficacy as an alternative therapeutic modality. Materials and methods: Laser fluence of 13 Joules (J)/cm2, 18 J/cm2 and 30 J/cm2 were used against several bacterial strains. Microwave dosages of 25, 50 and 100 watts (W) were used, respectively. Results: A significant difference between the three groups was observed using repeated analysis of variance (RANOVA) (F value: 0.74, and p value: 0.001). The Greenhouse−Geisser correction (GG) revealed significant results for laser irradiation alone. However, effect size calculation showed effects with microwave diathermy as well as laser fluence. Conclusions: Low-level laser therapy appears to be an effective modality of treatment when compared with continuous microwave diathermy on the Gram-negative and the Gram-positive bacterial strains tested. Microwave diathermy revealed large and medium effects on the bacterial cell counts with dominant effects on Gram-negative strains.